Analisis Faktor-faktor yang Mempengaruhi Harga Saham pada Perusahaan Sektor Pertambangan yang Terdaftar Indeks Saham Syariah Indonesia Tahun 2022-2023 - Aisah, Siti; Kurniawan, Bambang; Prasaja, Syukron (Al-DYAS, 2024)
This research aims to analyze the influence of macroeconomic variables and coal prices on mining company share prices in the Indonesian Sharia Stock Index (ISSI). Using quantitative data from 2022-2023 analyzed using panel data regression. The results show that simultaneously, macroeconomic variables and coal prices have a significant effect on stock prices. Partially, inflation, rupiah exchange rate, interest rates and coal prices have a significant negative influence on stock prices, while per capita income does not have a significant influence. The research model is able to explain 23.59% of stock price variations. These findings provide insight for investors, financial managers and policy makers about the factors that influence share prices in the Islamic mining sector.